FRESH WATER PRODUCTION IN COASTAL AND REMOTE AREAS BY SOLAR POWERED LIQUID-LIQUID MEMBRANE CONTACTOR - Heru Susanto; I G. Wenten (JOURNAL OF COASTAL DEVELOPMENT, 2003)
Liquid-liquid membrane contactor (LLMC) is a new desalination process using microporous hydrophobic membrane. The temperature difference at two solution-membrane interfaces gives rise to a trans membrane vapor pressure difference that drives the flux. In this work, the effect of process parameters on LLMC performance has been done. The process parameters consist of feed and permeate temperatures, cross flow velocity, feed concentration and mode of operation. In addition, this paper focuses on the development of LLMC by using solar and wind as energy sources. In this experiments micro porous hydrophobic hollow fiber polypropylene membrane with 0,2 mm was used as a contacting device. The experiment were conducted at temperature of 25-80oC, cross flow velocity of 0.02-0.2 m/s and solute concentration of 0-110.000 mg/L. Results show that the flux was influenced by the feed and permeate temperatures, the cross flow velocity and the concentration of solute. The increase of feed temperature increases the flux exponentially, whereas the flux seems to increase linearly with the increase of cross flow velocity. On the other hand, the flux was not significantly affected by the solute concentration. Furthermore, the flux in the counter current mode was lower than in the co-current mode. The average pure water fluxes obtained were in the range of 2-3 l/(m2h), whereas the products concentrations were in the range of 2-5.3 mg/L depending on the feed concentration. The operation of solar powered LLMC up to 10 days shows a very stable performance.